"They Need to Hear Our Voices": A Multidimensional Framework of Black College Women's Sociopolitical Development and Activism. (May 2022) - Leath, Seanna; Ball, Paris; Mims, Lauren; Butler-Barnes, Sheretta; Quiles, Taina
Black women have played an integral role in Black liberation struggles. Yet there is little psychological scholarship on Black women's contribution to social justice movements, particularly beyond conventional forms of activism, such as protesting and voting. To address this gap, the current study draws on Black feminist epistemology to present a multidimensional framework of Black college women's sociopolitical development. Using consensual qualitative research methods, we analyzed semistructured interview data from 65 Black college women (18-24 years) to explore their understandings of agency, civic engagement, and resistance. Eight themes emerged— gaining knowledge, self-advocacy, sisterhood, self-love, educating others, collective organizing and leadership, community care, and career aspirations. Our results situate Black college women's activism within a sociohistorical framework of Black feminist organizing and underscore the overlapping roles of self-awareness, interpersonal relationships, and institutional knowledge. The authors discuss how the contemporary racial and sociopolitical climate in the United States informed the participants' social justice orientation and how their involvement and investment in the Black community helped the participants reframe racial violence and oppression into narratives of resistance and healing.